Articulates storyline media-based discovery learning for training students critical thinking skill - Fhina Noviyanti; Lulu Tunjung Biru; Septi Kurniasih (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Critical thinking skills are crucial skills to be mastered by students in the 21st century. Critical thinking skills are also needed in the learning process, one of which is science learning. The Articulate Storyline learning media was developed to overcome students' need for critical thinking skills in science lessons. The research carried out is a development research (R&D) based on the Borg and Gall development model conducted by the Puslitjaknov Team. This study aims to analyze the level of validation of the Articulate Storyline learning media based on discovery learning in science learning in training the critical skills of junior high school students. The instrument involved in this study was an expert validation test questionnaire. The data presented in the study are qualitative and quantitative. Material experts who received validation results reached 88% in the